The Effects of Pectinase and Amylase Enzyme on The Physicochemical Quality of Sisaket Lava Durian (Durio zibethinus Murray) Syrup - Musika, Jirayu; Sungin, Panarat; Musika, Thanawan (Journal of Food Technology, Siam University, 2025)
This study examines the impact of pectinase and amylase enzymes on the physicochemical properties of Sisaket lava durian syrup. The experimental setup utilized a Central Composite Design (CCD), with two primary variables: enzyme concentrations of pectinase and amylase, ranging from 0.05% to 0.20%. The findings revealed that both enzymes significantly affected the quality of the lava durian juice. The coefficient of determination (R²) values for the response variables were as follows: yield: 0.96, RSS: 0.99, clarity (%T670): 0.99, and reducing sugar: 0.82. The high R² values indicate that the model effectively captures the relationships between the variables. According to the response surface model, the optimal conditions for enzymatic lava durian juice production were: pectinase (X1) at 0.12%, amylase (X2) at 0.18%, with incubation at 50°C for 120 minutes. Under these conditions, the predicted response values were: reducing sugar at 10.58 g/100g, clarity (%T670) at 95.83%, RSS at 25.32 °Brix, and yield at 53.85%. The vacuum evaporation method at 60°C for 120 minutes was identified as the most suitable condition for syrup production, achieving the highest yield of 55.21%.